Environmental appraisal of ferrochromium slag as concrete pavement material. (2022) - Panda, Chittaranjan; Pujari, Anubha; Biswal, Sudhansu Sekhar; Jena, Trilochan; Pradhan, Nibedita; Mallick, Subrat Kumar
Abstract: Ferrochromium slag is a waste product in the production of ferrochromium alloy, an important constituent of stainless steel and others. Material characteristics of the slag has been found to be very suitable for civil construction purpose and particularly as road construction material. There is reported leaching of chromium from unbound waste slag at lower pH and finer size of the particles. Experimentally, it is demonstrated that under acid rain pH condition 3 and about 75-µm particle sizing, there is release of chromium about 55.4 –71.2 mg/l as hexavalent chromium and 234.2 –248.5 mg/l as total chromium, which will exceed the discharge standard by regulatory bodies. The manufactured concrete with slag as coarse aggregate has the strength more than 20 % than that of normal concrete. Leachable chromium is suitably immobilized in cement and concrete medium with leachability index more than 12.5 validating the lower elution of chromium and complying with the regulatory requirement. Thus, instead of using unbound slag in road construction activities, concrete bound ferrochromium slag can be utilized in the construction of pavement.